2010
DOI: 10.1039/c0md00015a
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and biological evaluation of new cephalosporin-oxazolidinone conjugates

Abstract: Two cephalosporin-oxazolidinone conjugates were synthesized by incorporation of a carbamate linker at the 3′-position of the cephalosporin. These compounds show stability in aqueous media until specifically activated by a β-lactamase, and retain antibacterial activities profiles reflecting both the individual cephalosporin and oxazolidinone components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
(14 reference statements)
1
10
0
Order By: Relevance
“…However, when 2‐aminobenzophenone 1a was reacted with 4‐acetylmorpholine 2g , 3‐acetyl‐2‐oxazolidinone 2h , and 4‐acetylimidazole 2i , 6,12‐diphenyldibenzo[b,f][1,5]diazocine 8a was obtained as the only product with higher yields (34.0, 42.0, and 41.0%, respectively). Morpholine ( 2g ), oxazolidinone ( 2h ), and imidazole ( 2i ) moieties were chosen for applications in biological activity as they are often found in antibacterial drugs, but these results suggest that they inhibit the formation of quinolines.…”
Section: Resultsmentioning
confidence: 99%
“…However, when 2‐aminobenzophenone 1a was reacted with 4‐acetylmorpholine 2g , 3‐acetyl‐2‐oxazolidinone 2h , and 4‐acetylimidazole 2i , 6,12‐diphenyldibenzo[b,f][1,5]diazocine 8a was obtained as the only product with higher yields (34.0, 42.0, and 41.0%, respectively). Morpholine ( 2g ), oxazolidinone ( 2h ), and imidazole ( 2i ) moieties were chosen for applications in biological activity as they are often found in antibacterial drugs, but these results suggest that they inhibit the formation of quinolines.…”
Section: Resultsmentioning
confidence: 99%
“…In general, these β‐lactam antibiotics can inhibit bacterial cell wall synthesis by the inhibition of penicillin‐binding proteins and derange the activity of polymer peptidoglycan biogenesis machinery, which has been deactivated by bacterial beta‐lactamase to open the beta‐lactam ring. Previously, one class of the beta‐lactam antibiotics, cephalosporins/cefazolin, which possesses the core structure, 7‐aminocephalosporanic acid (7‐ACA), has been covalently conjugated with several small molecules to enhance and/or recover their biological activity, including oxazolidinone (at the C3’ position of 7‐ACA), quinolones (at the C3’ position), metallopolymers ( via ionic complexation), siderophore (C7 position substituent), and host defense peptide ( via a cleavable carbamate‐1,4‐triazole linker at the C3’ position) . Interestingly, a report showed that a number of amino acids or dipeptides attached via their C‐terminal carboxylates to the 7‐amino group of 7‐ACA was sufficient to result in significant antibacterial activity when the amino acids or dipeptides alone had none .…”
Section: Introductionmentioning
confidence: 99%
“…reported enhanced antibacterial activity for some cephalosporins with a carbamate derivatization, whereas Yan et al. incorporated a linezolid‐like moiety to obtain cephalosporin–oxazolidinone conjugates . In this respect, we also designed, synthesized and evaluated two β‐lactam carbamates armed with a linezolid‐like molecular fragment.…”
Section: Introductionmentioning
confidence: 99%